Sistem Pendukung Keputusan Pemilihan Rumah Terbaik Di Daerah Medan Johor Menggunakan Metode SMART - Nasution, Fajriansyah Maulana; Suriati, Suriati; Syahputri, Nenna Irsa (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2022)
House is one of the most basic human needs where house is a place for shelter and ongoing activities as well as an investment. Selection of houses needs to be done in order to get the best alternative houses that match the criteria of prospective buyers, selection of houses based on many aspects such as price, land area, house space, public services, environment, location, road access, facilities and other aspects. Therefore, in this study, a web-based decision support system application was built to decide the best house based on decided aspects. The decision support system was built using the SMART (Simple Multi Attribute Rating Technique) method. This method has a working method based on the theory that each alternative consists of several criteria that contain a number of sub-criteria that have a value and each criterion has a weight to describe how important its value is compared to other criteria. The results obtained in this study are the obtaining of the best house alternative based on the criteria and weight values that have been determined by the user using a decision support system that has been built. Keywords: House, Decision Support System, SMART, Web, Criteria